APLIKASI SENSOR NTC 47D-15 DAN SENSOR KELEMBABAN 808H5V5 PADA MESIN PENGERING DAUN SUNGKAI - Pola Risma (Elektron : Jurnal Ilmiah, 2013)
Nowdays, the production of herbal medicines to industrial scale household progressively increased as the emergence of the phenomenon in the society for the re-use of natural medicines / herbal derived from plants as one solution to health. In order for the herbal medicines are not easily damaged and can be stored for a long time, the drying process is carried out at a temperature of 300C–90oC (Depkes RI, 1985). The herbal medicine used in this study is the Sungkai leaves which is dried using dryer that applies NTC temperature sensor 47D-15, 808H5V5 humidity sensors, and microcontroller ATMega 8535. NTC sensor 47D-15 serves to detect the temperature to be set at the desired range during the drying process occurs while the humidity sensor 808H5V5 detects moisture of Sungkai leaves after the drying process.